A First Glimpse of Wild Lupin Karyotype Variation As Revealed by Comparative Cytogenetic Mapping - Susek, Karolina; Bielski, Wojciech K.; Hasterok, Robert; Naganowska, Barbara; Wolko, Bogdan (Frontiers in Plant Science, 2016)
Insight into plant genomes at the cytomolecular level provides useful information about their karyotype structure, enabling inferences about taxonomic relationships and evolutionary origins. The Old World lupins demonstrate a high level of genomic diversification involving variation in chromosome numbers (2n=32-52), basic chromosome numbers (x=5-7, 9, 13) and in nuclear genome size (2C DNA=0.97-2.68 pg). Lupins comprise both crop and wild species and provide an intriguing system to study karyotype evolution. In order to investigate lupin chromosome structure, heterologous FISH was used. Sixteen BACs that had been generated as chromosome markers for the reference species, Lupinus angustifolius, were used to identify chromosomes in the wild species and explore karyotype variation. While all ‘single-locus’ in L. angustifolius, in the wild lupins these clones proved to be ‘single-locus’, ‘single-locus’ with additional signals, ‘repetitive’ or had no detectable BAC-FISH signal. The diverse distribution of the clones in the targeted genomes suggests a complex evolution history, which possibly involved multiple chromosomal changes such as fusions/fissions and repetitive sequence amplification. Twelve BACs were sequenced and we found numerous transposable elements including DNA transposons as well as LTR and non-LTR retrotransposons with varying quantity and composition among the different lupin species. However, at this preliminary stage, no correlation was observed between the pattern of BAC-FISH signals and the repeat content in particular BACs. Here, we describe the first BAC-based chromosome-specific markers for the wild species: L. cosentinii, L. cryptanthus, L. pilosus, L. micranthus and one New World lupin, L. multiflorus. These BACs could constitute the basis for an assignment of the chromosomal and genetic maps of other lupins, e.g. L. albus and L. luteus. Moreover, we identified karyotype variation that helps illustrate the relationships between the lupins and the extensive cytological diversity within this group. In this study we premise that lupin genomes underwent at least two rounds of fusion and fission events resulting in the reduction in chromosome number from 2n=52 through 2n=40 to 2n=32, followed by chromosome number increment to 2n=42.